Implementation of Good Corporate Governance in Cooperatives in Indonesia - Dwi Agustina; Mohamad Adam; Isni Andriana (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study examines the effect of Fairness Performance, Transparency Performance, Accountability Performance, Responsibility Performance, and Independency Performance on Financial Performance. The data were collected using a questionnaire distributed to 48 cooperatives fostered by Dinas Koperasi dan UKM Provinsi Sumatera Selatan. Province The data were analyzed using the Regression method with SPSS 23 software. The results of this study show that Fairness Performance, Transparency Performance, Accountability Performance, Responsibility Performance, and Independency Performance have positive and significant effect on Financial Performance.